And don't f&%k it up : an oral history of RuPaul's drag race (the first ten years) - Fernandez, Maria Elena (Grand Central Publishing, Hachette Book Group, 2023)
"The four-time winner of the Emmy for outstanding reality series, RuPaul's Drag Race never set out to win over conventional America or climb the ladder of mainstream pop culture success. Its first season was classic counterculture, developed and filmed while President G.W. Bush was in office but launched at a time when Obama fever was at a national high. Over thirteen years and about 160 drag queen contestants later, everything from its language and style has seeped into the culture, cementing its place in herstory, one tuck at a time. With viewers everywhere from the halls of Congress to Wall Street, from big cities to small towns, Drag Race has become a worldwide phenomenon. Told over its first ten years, encompassing the show's first 14 seasons, And Don't F&%k It Up tells a cultural history through the stories of the people who lived it: the creators of the show, the contestants, the crew, the judges, and even some key (famous) fans. It begins with RuPaul's 34-year friendship and business relationship with World of Wonder Productions, the entertainment company that helped launch him into superstardom, and later talked him into giving a drag reality show a chance. From there, it traces the evolution of the show--and its queens--through a decade of gag-worthy seasons, serving up all kinds of behind-the-scenes realness, from Ongina's decision to reveal her HIV+ status to the story behind Asia O'Hara's butterfly finale fiasco. With a history as shady and funny as it is dramatic and inspiring, RuPaul's Drag Race is a mirror reflecting the cultural and political mores of our time. Its meteoric rise to becoming a once-in-a-generation success story is explored here as never before, in intimate, exuberant, unfettered detail"--